Coastal Ecosystems: A Critical Element of Risk Reduction. Issue 3 (20th November 2013) - Spalding, Mark D.; McIvor, Anna L.; Beck, Michael W.; Koch, Evamaria W.; Möller, Iris; Reed, Denise J.; Rubinoff, Pamela; Spencer, Thomas; Tolhurst, Trevor J.; Wamsley, Ty V.; van Wesenbeeck, Bregje K.; Wolanski, Eric; et al.
Abstract The conservation of coastal ecosystems can provide considerable coastal protection benefits, but this role has not been sufficiently accounted for in coastal planning and engineering. Substantial evidence now exists showing how, and under what conditions, ecosystems can play a valuable function in wave and storm surge attenuation, erosion reduction, and in the longer term maintenance of the coastal profile. Both through their capacity for self repair and recovery, and through the often considerable cobenefits they provide, ecosystems can offer notable advantages over traditional engineering approaches in some settings. They can also be combined in "hybrid" engineering designs. We make 10 recommendations to encourage the utilization of existing knowledge and to improve the incorporation of ecosystems into policy, planning and funding for coastal hazard risk reduction.